Measuring Spiritual Well-Being in Brazilian Adolescents with Chronic Illness Using the FACIT-Sp-12: Age Adaptation of the Self-Report Version, Development of the Parental-Report Version, and Validation - de Alvarenga, Willyane Andrade (Journal of religion and health, 2019)
Spiritual well-being is a major issue in health care, but instruments for measuring this construct in adolescents are lacking. This study adapted the 12-item Functional Assessment of Chronic Illness Therapy-Spiritual Well-being Scale (FACIT-Sp-12) for use with Brazilian adolescents with chronic diseases and developed a parental observer-rated version, using an expert panel, back-translation, and cognitive interviews with 72 participants. The psychometric properties of both versions were verified with two- and three-factor models by testing with 212 participants. The self- and parental-reported versions showed face validity, content validity, and acceptable levels of internal consistency for the overall scale and the two-factor model. The convergent validity was satisfactory for most items in both two- and three-factor models, but there was a lack of discrimination in the three-factor model using multitrait-multimethod analysis. This study presents the first instrument to assess the spiritual well-being of adolescents from their point of view and to allow their parents to serve as evaluators. However, we recommend further psychometric testing of the self- and parental-report scales to assess spiritual well-being in adolescents with chronic diseases in Brazil.